In vitro comparison of cyclic fatigue resistance of TruNatomy in single and double curvature canals compared with different nickel-titanium rotary instruments - Amr M. Elnaghy; Shaymaa E. Elsaka; Ayman O. Mandorah (BMC, 2020)
Abstract Background The purpose of this study was to compare the cyclic fatigue resistance of newly developed TruNatomy instruments (TRN) in single and double (S-shaped) curvature canals with HyFlex CM (HCM), Vortex Blue (VB) and RaCe (RC) instruments. Methods Size 20/.04 taper and size 25/0.04 of HCM, VB and RC were used. For TRN instruments, size 20/.04 taper (small) and size 26/.04 taper (prime) were used. The instruments were tested in artificial canals with double curvature (coronal curve; 60° curvature, 5 mm radius and apical curve; 70° curvature and 2 mm radius) and single curvature (60° curvature, 5 mm radius). The number of cycles to failure (NCF) was recorded. Data were statistically analyzed by Kruskal-Wallis and Dunn's multiple comparison tests. Weibull analysis was performed on NCF data. Statistical significant was set at p < 0.05. Results TRN and HCM revealed higher NCF compared with the other instruments for both tested sizes in single and double curvature canals (p < 0.05). TRN and HCM showed no statistically significant difference in the NCF (p > 0.05). The probability of survival was higher for HCM and TRN instruments than VB and RC instruments. Conclusions HCM and TRN instruments were more resistant to cyclic fatigue than VB and RC instruments in single and double curvature canals. HCM and TRN instruments were anticipated to survive with higher number of cycles than the other tested instruments. RC instrument had the lowest fatigue resistance than the other instruments.